Epidemiology, healthcare utilization, and related costs among patients with IPF: results from a German claims database analysis - Kreuter, Michael; Picker, Nils; Schwarzkopf, Larissa; Baumann, Severin; Cerani, Agustin; Postema, Roelien; Maywald, Ulf; Dittmar, Axel; Langley, Jonathan; Patel, Haridarshan (Respiratory research, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive form of fibrosing interstitial pneumonia with poor survival. This study provides insight into the epidemiology, cost, and disease course of IPF in Germany.